Stages of change, barriers, benefits, and preferences for exercise in RA patients: a cross-sectional study. (2013) - Henchoz, Y; Zufferey, P; So, A
Abstract : Objectives: To determine the distribution of exercise stages of change in a rheumatoid arthritis (RA) cohort, and to examine patients' perceptions of exercise benefits, barriers, and their preferences for exercise. Methods: One hundred and twenty RA patients who attended the Rheumatology Unit of a University Hospital were asked to participate in the study. Those who agreed were administered a questionnaire to determine their exercise stage of change, their perceived benefits and barriers to exercise, and their preferences for various features of exercise. Results: Eighty-nine (74%) patients were finally included in the analyses. Their mean age was 58.4 years, mean RA duration 10.1 years, and mean disease activity score 2.8. The distribution of exercise stages of change was as follows: precontemplation (n = 30, 34%), contemplation (n = 11, 13%), preparation (n = 5, 6%), action (n = 2, 2%), and maintenance (n = 39, 45%). Compared to patients in the maintenance stage of change, precontemplators exhibited different demographic and functional characteristics and reported less exercise benefits and more barriers to exercise. Most participants preferred exercising alone (40%), at home (29%), at a moderate intensity (64%), with advice provided by a rheumatologist (34%) or a specialist in exercise and RA (34%). Walking was by far the preferred type of exercise, in both the summer (86%) and the winter (51%). Conclusions: Our cohort of patients with RA was essentially distributed across the precontemplation and maintenance exercise stages of change. These subgroups of patients exhibit psychological and functional differences that make their needs different in terms of exercise counselling.